2018
DOI: 10.3390/cosmetics5040065
|View full text |Cite
|
Sign up to set email alerts
|

ES2 as a Novel Verbascoside-Derived Compound in the Treatment of Cutaneous Wound Healing

Abstract: Several pathologies are characterized by chronic wounds and often resistant to many of the common therapies, leading to chronic infections that can become even life-threatening for patients. For this reason, the identification of new products able to ameliorate the healing process is still an on-going research. Natural compounds have been used to improve skin conditions due to their dermo-cosmetic and therapeutic activities including anti-inflammatory, antioxidant and cell-migratory properties. Among these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Likewise, the biological effects of the B. cordata cell culture methanolic extract at the highest tested concentration on fibroblasts were comparable to verbascoside ( Figure 1 b,c), thus, indicating the importance of the concentration in exerting significant biological effects. In other studies, the exposure of V79 fibroblasts and HaCaT keratinocytes to verbascoside over 24 h significantly reduced the cell viability by around 50% (78.8 and 31.23 µg/mL, respectively) [ 61 , 62 ]. This suggests that the cytotoxic effect of the verbascoside is caused by its ability to reduce the activity of cytoplasmic protein tyrosine phosphatases by binding to the Scr homology 2 (SH2) NH2-terminal domain (SHP1); these receptors are implicated in the growth, differentiation, and apoptosis of cells [ 37 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, the biological effects of the B. cordata cell culture methanolic extract at the highest tested concentration on fibroblasts were comparable to verbascoside ( Figure 1 b,c), thus, indicating the importance of the concentration in exerting significant biological effects. In other studies, the exposure of V79 fibroblasts and HaCaT keratinocytes to verbascoside over 24 h significantly reduced the cell viability by around 50% (78.8 and 31.23 µg/mL, respectively) [ 61 , 62 ]. This suggests that the cytotoxic effect of the verbascoside is caused by its ability to reduce the activity of cytoplasmic protein tyrosine phosphatases by binding to the Scr homology 2 (SH2) NH2-terminal domain (SHP1); these receptors are implicated in the growth, differentiation, and apoptosis of cells [ 37 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 96%
“…Verbascoside has been widely used in the cosmetics with potential anti-inflammatory, antioxidant and photoprotecting activities [41,42]. It has been previously shown that the topical application of a semi-synthetic derivative of this compound was able to promote the wound healing in rats [41].…”
Section: Discussionmentioning
confidence: 99%
“…The skin is an organ that has protective functions towards the external environment and its physical integrity is essential to accomplish its functions [11]. Skin aging might happen via two mechanisms: The first termed intrinsic or age dependent, is initiated by several factors, such as telomere shortening, free radicals and antioxidants imbalance and hormonal changes, while the second mechanism-photoaging is due to exposure of the skin to UV solar radiation [20].…”
Section: Extracts (Secondary Metabolites) Activities-gene Expression mentioning
confidence: 99%
“…The wound healing properties of the water-soluble verbascoside derived from the cell suspension of Buddeleia davidii were improved by the obtaining of its lipophilic semi-synthetic derivative ES2. The ES2 is considered as a novel and potent candidate for topical treatment of wounds, since this compound improved the wound closure more than 2-folds in HaCaT cells and SKH1 mice, compared to that of verbascoside at 10 μM concentration [ 11 ]. Another derivative of verbascoside, denoted as verbascoside pentapropionate, also exhibited lower hydrophilic profile and improved antioxidant activities than verbascoside [ 85 ].…”
Section: Extracts (Secondary Metabolites) Activities-gene Expressimentioning
confidence: 99%
See 1 more Smart Citation